Peculiarities of nanocrystalline silicon films growth on porous anodic alumina surface - Parfenyuk, P.V.; Evtukh, A.A.; Korobchuk, I.M.; Glotov, V.I.; Strelchuk, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
The influence of porous alumina template morphology on silicon film growth during deposition by PE CVD has been investigated. As it was shown, the structural properties of silicon phases depend on the pore geometry and surface morphology of the anodized porous alumina substrate. In the case of porous alumina formation in one stage, ripple-like morphology takes place. The growth of a-Si:H film is observed during deposition. After two-stage anodization, the porous alumina has a tipped/ribbed morphology. In this case, usually a-Si:H film grows on the bottom of the pores, and nc-Si:H/a-Si:H one grows on the tips. In the case of deep pores, the nanocrystalline nc-Si:H film grows only above the top of the pores. The obtained results could be used when developing new types of photocells, sensors, nanophotonics, and ionics devices.